Efektifitas buah bit terhadap peningkatan kadar hemoglobin ibu hamil - Syari, Mila; Oktafirnanda, Yuka; Effendy, Yulida; Harahap, Novy Ramini (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Introduction: Anemia is a situation wherein the variety of blood cells inside the frame is small; as a result, the distribution of oxygen at some stage in the frame is delayed. The mom reviews anemia if the hemoglobin stage drops or is extraordinary if it's miles 11gr%. One of the reasons for anemia throughout pregnancy is iron deficiency. Consuming beetroot juice can assist in hemoglobin degrees in anemic pregnant ladies. The intention of this take a look at became to decide the impact of giving beetroot juice on growing Hb in pregnant ladies within the 1/3 trimester. This study technique is a quasi-experimental study with an unmarried institution, pre-taking a look at the design and post-taking a look at it. The populace of this looks at all anemic pregnant ladies within the 1/3 trimester from March to July 2023, totaling 15 pregnant ladies. In this, take a look at the pattern of 15 pregnant ladies with the usage of the general sampling technique. The information used is number one and secondary information. Data had been analyzed through the usage of paired t take a look at the analysis. Results: The study consequences display a paired t fee of 4.036 and p-fee=0.001, which proves that p-fee=0.001andlt; α=0.05, so Ha is ordinary and Ho is rejected; because of this, giving beetroot juice has an impact on growing Hb in 1/3 trimester pregnant ladies. Conclusion: From this, it may be concluded that giving beetroot juice will increase Hb in 1/3 trimester pregnant ladies. It is hoped that the consequences of this study will permit 1/3 trimester pregnant ladies to eat beetroot juice or different hemoglobin-growing meals each day.